The narrative and moral discourse regarding marriage in Tobit - Beck, Boris (Array, 2018)
Tobit was written around the third century B.C. It is considered canonical by the Catholics and the Orthodox believers, but not by Protestants and the Jews. The story is not historical but fictional, with a very dynamic narrative, containing numerous lessons in the spirit of the OT, particularly those relating to Deuteronomy theology. The central theme of the book is marriage and the ideal marriage is portrayed in terms of physical purity, struggling against lust, faithfulness, monogamy, and the permanence of the marriage covenant. It is pointed out in many places that love, fondness, and consideration are necessary for a successful marriage. Another important condition is the endogamy of marriage, so that the spouses would be able to keep and practice their faith more easily. And finally, prayer as the expression of trust in God is posited as the foundation of a marriage whose purpose transcends the erotic and procreative functions and emphasis is also placed on the importance of consecration. So in a fun way, Tobit offers a moral lesson which ties in with Biblical morality.